Power-differentiated Emotions of Populist Support: Regional Anger and Classed Fear in Duterte’s Philippines - Uyheng, Joshua (Archīum Ateneo, 2021)
Extensive studies link anger; fear; and support for populist leaders; but prevailing approaches largely assume an individual model of emotion. In this exploratory short report; we invoke a structurally sensitive social psychological account of the group-based and power-laden dynamics of populist emotion. Analyzing a stratified sample of Philippine respondents; we investigate how anger and fear interact with memberships in low- and high-power classed and regional groups in predicting support for populist President Rodrigo Duterte and various policies of his regime. Lower levels of regional and classed power intensified the association between emotions and populist support. Power-laden complications were also detected on the policy level. We discuss the implications of this work in terms of contextualizing political emotions within local configurations of unequal intergroup relations.